Preharvest sodium selenite treatments affect the growth and enhance nutritional quality of purple leaf mustard with abundant anthocyanin - Wang, Bin; Yuan, Xiao; Wang, Guang; Zhu, Yun-na; Zhou, Run-chang; Feng, Hui-min; Li, Hai-bo (Frontiers in Nutrition, 2024)
Both selenium (Se) and anthocyanins are crucial for maintaining human health.Preharvest Se treatments could promote anthocyanin biosynthesis and augment Se levels in vegetables, helping to combat Se deficiencies in dietary intake. However, it remains unknown whether preharvest Se treatment could balance growth and anthocyanin biosynthesis in plants and what the appropriate treatment concentration is.In this study, preharvest treatments with sodium selenite at varying concentrations (0, 5, 10, and 30 mg/kg) affect the growth and nutritional quality of purple leaf mustard (Brassica juncea) with abundant anthocyanins. Lower Se concentrations (≤ 10 mg/kg) preharvest treatments enhanced photosynthesis, facilitated root system development, consequently elevated the biomass. Conversely, higher Se levels (≥ 30 mg/kg) reduced photosynthesis and biomass. The dosage-dependent effects of Se treatments were corroborated through seedlings cultivated in hydroponic conditions. Moreover, nearly all Se treatments elevated the contents of various nutrients in leaf mustard, particularly anthocyanin and organic Se. These results suggest an overall enhancement in nutritional quality of leaf mustard plants. Furthermore, the application of 10 mg/kg Se significantly enhanced the activity of phenylalanine ammonialyase and upregulated the expression of 12 genes pivotal for anthocyanin biosynthesis, further demonstrating the fortified effects of Se enrichment on anthocyanins in leaf mustard. Low-level Se treatments resulted in heightened antioxidant activity (APX, CAT, and POD), mitigating reactive oxygen species induced by increasing Se content 3 in tissues. The enhanced antioxidant activities may be beneficial for the normal growth of leaf mustard under Se stress conditions. In conclusion, our study demonstrated preharvest Se treatment at 10 mg/kg could balance the growth and anthocyanin biosynthesis in purple leaf mustard. This study offers valuable insights into anthocyanin fortification through Se enrichment methods in agricultural practices, ensuring that such fortification does not compromise vegetable yield.